â€œMATTER OF CONCERNâ€ PABRIK ES ALWI ASSEGAF PALEMBANG SEBAGAI BANGUNAN HERITAGE - Rizal, Randy; Ekomadyo, Agus S. (Jurnal Koridor, 2021)
ABSTRACT As one of the oldest cities in Indonesia, Palembang has a history related to the Musi river. The Musi River divides the city of Palembang into Ilir and Ulu. This river was known as a trade route in ancient times, so that many Chinese and Arab immigrants settled on the riverbank. In the Ulu, there are several village areas that are mostly inhabited by Arab residents, one of which is Assegaf Village. This study will specifically discuss the Assegaf village, especially its famous icon, the Alwi Assegaf ice factory. This factory is an integral part of the life chain of the Musi river. Many traditional fishermen rely on the ice factory and it is clear that the Alwi Assegaf ice factory has an impact and influence on residents. The purpose of this research is to explore further history, cultural ideas and actors who play a role in the Alwi Assegaf ice factory. It also aims to reveal the identity of the ice factory itself against the socio-economic conditions in Assegaf Village residents. The research method was carried out qualitatively in the form of interview, field observation and literature reviews. The elements discussed will use the ANT (Actor-Network Theory) method to obtain a mapping description of the actors involved in the daily production of the Alwi Assegaf ice factory. The contribution of this study can be used as a review of further research literature that focuses on actor-network theory analysis. Keywords: Actor-Network Theory, Actor, Assegaf Village, Ice Factory. Relation